ToxRefDB v2.1: update to curated in vivo study data in the Toxicity Reference Database - Feshuk, Madison; Kolaczkowski, Lori; Watford, Sean; Paul Friedman, Katie (Frontiers in Toxicology, 2023)
The Toxicity Reference Database (ToxRefDB) contains in vivo study data from over 5,900 guideline or guideline-like studies for over 1,100 chemicals. The database includes information regarding study design, chemical treatment, dosing, treatment group parameters, treatment-related (significantly different from control) and critical (adverse) effects, guided by a controlled effect vocabulary, as well as endpoint testing status according to health effects guideline requirements. ToxRefDB v2.1 is an update to address a compilation error found in ToxRefDB v2.0 that resulted in some effects being inadvertently omitted from the database. Though effect data has been recovered, no new studies were added. The recovered data improves the utility of ToxRefDB as a resource for curated legacy in vivo information, which enhances scientific confidence in vitro high-throughput screening of chemicals and supports retrospective and predictive toxicology applications for which outcomes in traditional regulatory toxicology studies serve as reference information.